Rotation thromboelastometry (ROTEM) enables improved outcomes in the pediatric trauma population - Deng, Qin (J Int Med Res, 2018)
OBJECTIVE: We evaluated the role of rotation thromboelastometry (ROTEM) in managing acute traumatic coagulopathy in pediatric patients with trauma. METHODS: A retrospective cohort of pediatric patients with trauma from six institutes was studied during a 10-year period from 2007 to 2017. The associations between ROTEM-guided, goal-directed coagulation therapy and clinical outcomes were determined. RESULTS: Three hundred thirty-two pediatric patients (age < 15 years) who were treated with ROTEM-guided, goal-directed coagulation therapy were matched to 332 control pediatric patients with conventional plasmatic coagulation tests. The ROTEM protocol was associated with a significant reduction in the interval for admission to acute traumatic coagulopathy treatment, less plasma transfusions in the first 24 hours of admission, and a favorable coagulopathy recovery. Furthermore, the median number of total hospital days was significantly shorter for patients who had the ROTEM protocol than for control patients. CONCLUSIONS: There are significant favorable outcomes, including rapid acute traumatic coagulopathy treatment and a lower 24-hour blood product requirement, following ROTEM-guided, goal-directed coagulation therapy among pediatric patients with blunt trauma.